HUBUNGAN BREEDING PLACE, KEBERADAAN RESTING PLACE DAN PRAKTIK 3M PLUS DENGAN KEJADIAN PENYAKIT DEMAM BERDARAH DENGUE (DBD) - Sety, La Ode Muhamad; Sutiswa, Shandra Isasi; Dewi, Riana; Ohorella, Arfan; Yoyoh, Imas (Ensiklopedia of Journal, 2024)
Abstract: Dengue fever is a disease caused by the dengue virus and transmitted by the Aedes aegypti mosquito. From 2020 to 2022, both the number of cases and mortality rates have decreased, but dengue fever is still spread across all 20 Puskesmas in Jambi City. During the last three years, Rawasari Health Center has the highest prevalence of dengue fever cases at 0.031%. The purpose of the study was to determine the relationship between breeding places, the presence of resting places and the practice of 3M plus with the incidence of dengue hemorrhagic fever (DHF). The type of research is quantitative with a case control approach. The research was conducted at the Rawasari Health Center. The population is the number of DHF patients in the working area of the Rawasari Health Center in 2022 as many as 16 cases. The sample in this study taken was 16 respondents. Where in this study using a ratio of 1: 2 between case and control, so that the case sample is 16 cases and 32 controls, it is known that the total number of samples is 48 samples. The sampling technique used total sampling. Data analysis was carried out univariate and bivariate. The results showed that there was a relationship between breeding places (p value: 0.001) and 3M plus practices (p value: 0.000) to the incidence of DHF. It is suggested that the community can utilize and recycle used goods around the house so as to minimize the opportunity for mosquitoes to breed in used goods and increase the practice of 3M plus.Keywords: Breeding Place, DBD, Praktik 3M Plus